Wind-induced tension and deflection of multi-span bundled transmission conductors using aeroelastic model wind tunnel test. (1st April 2022) - Song, Jie; Liang, Shuguo; Mei, Xiaohan; Zou, Lianghao
Highlights: A large-size aeroelastic model of two-span six-bundled conductors is fabricated. Wind-induced tension and deflection of the insulator are measured by wind tunnel test. CFy decreases with increasing θ and VH, and is close to 1.0 when θ = 90° and VH > 35 m/s. Length of insulator increases the transverse tension while decreases the swing angle. GB50545 and GB50655 overestimates force coefficient for multi-span bundled conductors. Abstract: An aeroelastic model of the two-span six-bundled conductors is fabricated without distortion of conductors, to investigate the performance of wind-excited multi-span transmission conductors. The wind tunnel test is conducted in a wind tunnel with a big size of cross-section to contain the large aeroelastic model of multi-span transmission conductors and measure wind-induced tension and deflection of the insulator. The effects of wind direction, wind speed, and length of insulator on the wind-induced tension and swing angle of the insulator are then investigated based on the wind tunnel measurement. Results show that the mean transverse tension increases with wind direction θ and follows the law of sin 2 θ when θ > 40°, but is not proportional to the square of mean wind speed VH when VH < 35 m/s. The force coefficient of the tension decreases with increasing θ and wind speed, and is close to 1.0 when θ = 90° and VH > 35 m/s. Swing angle of the insulator increases with θ and VH, and follows the law of sin θ when θ > 40°. The dynamic response component of the insulator's swing angle is insignificant when VH > 30 m/s. The length of insulator tends to increase the transverse tension while decrease the swing angle of the insulator. In addition, the wind force coefficient from the aeroelastic model of the two-span conductors is smaller than that specified in GB50545 and GB50655, indicating that these two might overestimate the wind loads on multi-span multi-bundled conductors.